Downton Abbey. Season 4 [videorecording (DVD)] - Fellowes, Julian (PBS Distribution, 2014)
1922. Six months after Matthew's tragic death, his loss is still felt throughout Downton Abbey. Mary struggles to face a new future with her fatherless child, and is encouraged by the family to pick up the pieces. Accepting a new role on the estate, the now-eligible Mary also finds herself the reluctant object of attention from a number of eager suitors. With the twenties in full swing and the tides of change sweeping through Downton, Rose's continued attraction to the bright lights of London spells trouble for the Crawleys, and Edith's budding relationship with Michael Gregson is threatened by events beyond her control. Meanwhile, below stairs, passions run high and young hearts look set to be broken.